Trinity International Development Initiative: Submission on International Development Policy – Public Consultation Paper - Murphy, Susan; Gilligan, Robbie; Wylie, Gillian; Browne, Brendan Ciaran; Dunwoody, George (My University, 2018)
Trinity International Development Initiative - TIDI 2 Introduction: This submission includes observations, feedback and recommendations on Ireland’s New International Development Policy Public Consultation Paper on behalf of Trinity International Development Initiative (TIDI). We enthusiastically welcome the opportunity to review, and to provide input into, the International Development Policy at this crucial early stage of formulation. We believe that the recognition of the role of the academic research and higher education community in Ireland as key stakeholders is essential for the successful formulation and implementation of national strategies, priorities and policies. The vision of the new policy is bold and ambitious. Already recognized for excellence and best practice by peer states, Ireland’s new development policy and approach could (and should) become a leading influence on the global stage. Development of this new policy offers the opportunity to scan the horizon and search for new ways of designing, managing and monitoring processes. It also offers scope to increase crucial citizen engagement in the search for new solutions, at national and international levels. The submission begins with an overview of our key messages and then provides responses to the specific questions raised in the International Development Policy – Public Consultation Process.
TIDI Submission
Transforming Our World: Help Ireland Make A Difference (New International Development Policy – 2018)
PUBLISHED
Keywords: International Development; Development Practice; International Development; Development; Policy